Stereotypic Conceptions vs. Perceptions of Expert Counsellor Behaviours - Khan, Janet A.; Gross, Darryl G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Similarities and differences were investigated between subjects' existing con- ceptions of counsellor characteristics and behaviours, and their subsequent percep- tions of these same characteristics and behaviours following videotaped samples of two counselling interactions represented by Rogers and Ellis who demonstrated client-centered and rational-emotive therapy. Both conceptions and perceptions were assessed by means of the Counselor Rating Form (CRF), and the Barrett- Lennard Relationship Inventory (BLRI). ANOVA results indicated that while subjects' existing conceptions and their subsequent perceptions of counsellor characteristics (e.g. attractiveness, expertness and trustworthiness) were largely congruent, in contrast, subjects' conceptions of counsellor behaviours (e.g. empathy, and level of regard) were much lower than their actual perception of the presence of these factors in counselling. The potential role of the socially stereotypic aspects of counsellor role and functions in subjects' perceptions cannot be overlooked.